2015
DOI: 10.1021/jf504710r
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Assessment Reveals an Elevated Level of Glucosinolate Content in CaCl2 Treated Broccoli Microgreens

Abstract: Preharvest calcium application has been shown to increase broccoli microgreen yield and extend shelf life. In this study, we investigated the effect of calcium application on its metabolome using ultra-high-performance liquid chromatography with mass spectrometry. The data collected were analyzed using principal component analysis and orthogonal projection to latent structural discriminate analysis. Chemical composition comparison shows that glucosinolates, a very important group of phytochemicals, are the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 52 publications
2
46
0
2
Order By: Relevance
“…Sun et al. () found that glucosinolates were the main compounds in broccoli microgreens that were enhanced by 10 mM calcium chloride preharvest treatment. Lu et al.…”
Section: Other Nutritional Facetsmentioning
confidence: 99%
“…Sun et al. () found that glucosinolates were the main compounds in broccoli microgreens that were enhanced by 10 mM calcium chloride preharvest treatment. Lu et al.…”
Section: Other Nutritional Facetsmentioning
confidence: 99%
“…However, if treated by 10 mmol · L -1 CaCl 2 before harvest, the shelf life can be extended to 14-21 d due to stimulated superoxide dismutase and peroxidase activities, lowered tissue electrolyte leakage, improved overall visual quality, and reduced microbial growth during storage (Kou et al, 2014a). A chemical composition comparison showed that glucosinolates, a very important group of phytochemicals, were the major compounds enhanced by preharvest treatment with 10 mmol · L -1 CaCl 2 (Sun et al, 2015). This study compares the effects of preharvest spray with CaCl 2 , Ca lactate, or Ca AA chelate, and a postharvest dip in Ca lactate on the quality and shelf life of broccoli microgreens.…”
mentioning
confidence: 99%
“…The UHPLC‐ESI/ITMS was performed according to a previously reported laboratory procedure (Sun et al, 2015). In brief, a LC/MS system consisting of an Agilent 1200 UHPLC system with a binary pump, a diode array detector (DAD), a vacuum degasser, a column oven, and an autosampler (Agilent Technologies) in combination with a LCQ Deca ion‐trap mass spectrometer (Thermo Fisher Scientific Inc.) was used for both LC and MS spectrometry.…”
Section: Methodsmentioning
confidence: 99%